ACTUAL PROBLEMS OF PERSONALITY FORMATION IN THE PERIOD OF YOUTH - Kateryna Lysenko-Gelembiuk (Vasyl Stefanyk Precarpathian National University, 2018)
The article reveals the phenomenology of adolescent age, from the point of view of ambivalence, psychological intensity and complexity of the marked period, as well as unquestionable significance in the personal formation of a young person.The present time dictates new rules, requirements for a strategy of life, which in turn require lability, speed of psychic response, and the realization of human potential, including, without exception, all spheres of being. Undoubtedly, ambitious goals, the desire to find and realize their own way, declare themselves, succeed, "build" their lives, cause the corresponding psychophysiological and social responses of the body of a young person.The purpose of the message is to update the issues of personal self-determination and becoming a youthful age, since it is the age-old age we consider to be the key to person`s self-realizing. From the point of view of qualitatively new accents, potential prospects and possibilities of their realization in the dimension of human life.The determining social task of adolescence is the choice of profession, social and personal self-determination. It is about the formation (a certain level of formation) of a complex of properties, abilities, needs, goals, orientation of the individual in general, which would allow the young man to fully self-realization in work, public life, future family. In this context, it is important to develop viability, the need and ability to communicate, and the development of reflection, which provides a conscious and critical attitude to itself [134; with. 105], [56; with. 92].It is sometimes difficult for a young person to balance the needs, desires, motives and goals, aspirations and beliefs, on the one hand, and social models, requirements and specifications on the other. The feeling of external pressure causes the inclusion of protective mechanisms of the psyche, often causing the reaction of resistance. Numerous cultural, political, ideological patterns, fashion, so-called modernity can cause a variety of psychophysiological reactions of the body (stress, depression, psychosomatic disorders, etc.).Trying to gain stability and security in extreme life conditions, a person, relying on internal and external resources, finds out an individual way of effective life balancing. At certain periods of life, it may be more effective to take patiently all the difficulties and difficulties, or to maximize mobilization and activity. Under the condition of the formation of these qualities, the development of skills in the constructive construction of interpersonal relationships, the young man has the necessary psychological basis for self-determination - the central tumor of the young age. Its basis is the need to take on the internal position of an adult, to realize himself a member of society (a sense of necessity), to know and understand oneself, their possibilities, their place and purpose in life. A high level of self-awareness stimulates interest in one's own personality, in the forms of its organization and self-regulation.The main psychological achievement of youth is its own inner world, the crystallization of ideas about himself- the integrative processes of the development of the I-concept; the formation of the general emotional orientation of the individual, that is, the consolidation of the hierarchy of their own values, certain experiences.Thus, the expansion of the self-I, changes in the perception of the "I" of another person, as a result of the person goes to a qualitatively new level of reflection of reality and adaptation to it, serving as a gain and already a mechanism for constructing the perspective of the picture of life and Himself in it. It is impossible to overestimate the psychological significance of adolescence in the personal formation of a person. After all, here, apparently, all, without exception, types of human activity are present, an opportunity not only to feel qualitative psycho-physiological, social changes, but also to realize them, to operate them, to use, to apply, etc. Become an architect and author of your life, with an extraordinary "taste" of the future, prospects, chances and potential opportunities, freedom of choice.Prospects for further research we see in the search for regulatory mechanisms for the implementation of the personality potential during the youth, which, of course, include hardiness, the vitality of the individual in a variety of manifestations of the concept. We consider it expedient on this basis to develop and verify the system of individual and group training on the development of key regulatory mechanisms for self-determination, self-expression and realization of its own resources in all spheres of life of a young person. Key words: youth, youth age, personal self-determination, life stability, socialization, role conflict, interpersonal conflict, empathy.